Once were Warriors – a Model that Matters and a Mirror of Concerns - Ramstad, Jorun Bræck (Nordlit, 2012)
In  this  article,  I  will  focus  on  connections  between  media,  culture and society  in order to understand two prototypical Maori responses to the film. The two kinds of responses are captured in the following phrases: “The film should never have been made” and “That’s not fiction, that’s reality”. One of my objectives is to show how these particular Maori responses to this fiction-film are entangled with deep concerns about  ethnic  policies  and marginalization  in  general.  In  other  words,  the  film  is explored  as  a statement  about  Maori  –  Pakeha  inter-ethnic  relations  and ‘biculturalism’, which is the official term for the political  vision of the post-colonial nation. Subsequently, my analysis suggests insights from a deeper concern about the contexts  that  contribute  to  these  particular  Maori formulations  of  media-reality configurations, in addition to lessons of a more general character.